Tun Dr. Mahathir’s leadership communication: the Confucian perspective - Cheah, Joyce Lynn-Sze; Yusof, Norhafezah; Ahmad, Mohd Khairie (EDP Sciences, 2017)
The main objective of this study is to explore the efficiency of utilizing a culturally - enhanced serious game in education particularly in Information Technology course.To attain this objective, the academic achievement of 61 participants was measured by using quantitative Quasi Experimental research design approach. Sets of pre- and post-test questions were administered to all participants, where descriptive analysis and hypothesis evaluation were performed to the collected data.The finding revealed that there were significant increase on the mean values of participants who played culturally-enhanced serious game as compared to those who played contemporary serious game (M= 3.00).Therefore, the study suggested that culturally-enhanced serious game has potential to support education particularly in Information Technology course.